Analisis Buku Matematika Kurikulum 1975 dan Kurikulum 2013 - Muhammad Taqiyuddin (Pusat Pengembangan dan Pemberdayaan Pendidik dan Tenaga Kependidikan Matematika, 2020)
This study examines Indonesian mathematics textbooks written based on the 1975 curriculum and the 2013 curriculum. This study analyses the physical characteristics, development process, topics breakdown, and contents characteristics of the textbooks. In analyzing the data, the researchers applied content analysis method. Based on the analysis results, it can be inferred that there are some aspects in the 2013 curriculum textbooks should be appreciated, for example, how a Mathematical concept is explained by applying several approaches, varied book references, details of the writer's profile, and examples of varied problems. Nonetheless, there are a number of things need to be continually improved such as the well-prepared trial testing, students’ activities adjustments listed in the textbooks, appropriate and real illustrations. Furthermore, the writers invite all parties to make such eforts that Indonesian Mathematics textbooks in the future may adjust and leverage the latest technological updates.